2018
DOI: 10.1038/mi.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

ICOS protects against mortality from acute lung injury through activation of IL-5+ ILC2s

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease causing irreversible lung scarring and loss of pulmonary function. IPF Patients suffer from a high rate of pulmonary infections and acute exacerbations of disease that further contribute to pulmonary decline. Low expression of the inducible T-cell costimulatory molecule (ICOS) in peripheral blood mononuclear cells predicts decreased survival of IPF patients, but the mechanisms by which ICOS protects are unclear. Using a model of bleomycin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…A growing body of evidence indicates that release of amphiregulin during innate type 2 responses is critical for suppressing inflammation and inducing tissue repair (30). IL-13 and IL-5 have both been demonstrated to protect against acute lung injury, and several recent studies have noted that type 2 cytokines may be protective during sepsis (21,(31)(32)(33)(34)(35). Consistent with these studies, we observed that treatment with IL-5 and IL-13 rescued PLZF -/mice from sepsis, indicating that 1 potential mechanism of IL-33mediated protection is through ILC2 cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of evidence indicates that release of amphiregulin during innate type 2 responses is critical for suppressing inflammation and inducing tissue repair (30). IL-13 and IL-5 have both been demonstrated to protect against acute lung injury, and several recent studies have noted that type 2 cytokines may be protective during sepsis (21,(31)(32)(33)(34)(35). Consistent with these studies, we observed that treatment with IL-5 and IL-13 rescued PLZF -/mice from sepsis, indicating that 1 potential mechanism of IL-33mediated protection is through ILC2 cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry analysis. Lungs were processed as previously described (32). Briefly, perfused lungs were minced and digested with 150 U/ml Collagenase D (Gibco) for 1 hour in DMEM supplemented with 5% FCS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…by inducing and regulating Th1, Th2, Th17 and innate lymphoid cell populations. [20][21][22][23][24] Furthermore, recent studies suggest that ICOS-mediated costimulation promotes B-cell differentiation and IgE production. 25 However, little is known about the effects of ICOS/ICOSL in Th22 cell development and AD.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Over the last two decades, ICOS has been reported to contribute to the pathogenesis of many immune disorders such as cancer, pulmonary sarcoidosis and allergic rhinitis, e.g. by inducing and regulating Th1, Th2, Th17 and innate lymphoid cell populations . Furthermore, recent studies suggest that ICOS‐mediated costimulation promotes B‐cell differentiation and IgE production .…”
mentioning
confidence: 99%